Identification of fault location for simultaneous fault in distribution system using discrete wavelet transform - Pothisarn, C.; Jettanasen, C.; Ngaopitakkul, A.; Apisit, C. (My University, 2011)
Currently, the most effective technique for identifying fault location, based on a travelling wave, has been proposed in several research papers. However, the effects of simultaneous faults have been neglected. In order to overcome this problem, a new algorithm will be developed in order to predict fault location precisely. This paper presents a technique to detect fault locations, during simultaneous fault, in an underground distribution system using discrete wavelet transform (DWT). The DWT is used to detect the high frequency components. The time that the fault signal uses to reach the ends of the distribution line is considered, then, applied so that the distance of fault can be calculated. The result is found that the proposed algorithm gives satisfactory both in case of single fault and simultaneous fault. ICIC International © 2011.
Keywords: Cable; Distribution; Fault location; Simultaneous fault; Wavelet transform